Controlling the dynamics of electrons and nuclei in ultrafast strong laser fields - Kling, Nora G. (Kansas State University, 2013)
One ultimate goal of ultrafast, strong- field laser science is to coherently control chemical reactions. Present laser technology allows for the production of intense (>10[superscript]13 W/cm[superscript]2), ultrashort ( 5 fs), carrier-envelope phase-stabilized pulses. By knowing the electric field waveform, sub-cycle resolution on the order of 100's of attoseconds (1 as=10[superscript]-18 s) can be reached -- the timescale for electron motion. Meanwhile, the laser field strengths are comparable to that which binds electrons to atoms or molecules. In this intense-field ultrashort-pulse regime one can both measure and manipulate dynamics of strong-field, quantum-mechanical processes in atoms and molecules. Despite much progress in the technology, typical durations for which lasers can be reliably locked to a specific carrier-envelope phase ranges from a few minutes to a few hours. Experiments investigating carrier-envelope phase effects that have necessarily long data acquisition times, such as those requiring coincidence between fragments originating from the same atom or molecule, are thus challenging and uncommon. Therefore, we combined the new technology for measuring the carrier-envelope phase of each and every laser shot with other single-shot coincidence three-dimensional momentum imaging techniques to alleviate the need for carrier-envelope phase stabilized laser pulses. Using phase-tagged coincidence techniques, several targets and laser-induced processes were studied. One particular highlight uses this method to study the recollision process of non-sequential double ionization of argon. By measuring the momentum of the two electrons emitted in the process, we could study their energy sharing. Furthermore, by selecting certain carrier-envelope phase values, and therefore laser pulses with a particular waveform, events with single recollision could be isolated and further analyzed. Another highlight is our studies of carrier-envelope phase effects in the dissociation of the benchmark H[subscript]2[superscript[+] ion beam. Aided by near-exact quantum mechanical calculations, we could identify interfering pathways which lead to the observed spatial asymmetry. These and other similar experiments are described in this thesis as significant steps toward their ultimate control.
Keywords: Atomic; Ultrafast laser studies; Strong field laser studies; Molecular optical physics; Atomic Physics (0748); Molecular Physics (0609); Physics (0605)